KONSEP DIRI REMAJA DALAM FILM INDONESIA: ANALISIS WACANA ATAS FILM REMAJA INDONESIA TAHUN 1970-2000-AN - Noviani, Ratna (Jurnal Kawistara, 2011)
Film is a system of representation, which provides information of social dynamics during the period, when the film is produced and distributed. This study is aimed to identify and reveal how teenage selfconcept is discursively constructed through film imagery and narrative in the context of Indonesian society. This study focuses particularly on the physical and psychological teenage self-concepts. The analytical Corpus is eight films for teenagers which were produced from the 1970s through the 2000s.Through the application of Norman Faircloughâs critical discourse analysis, a detailed examination of these films reveals that there are similarities, modification and differences in the way in which teenage self-concept has been constructed from decade to decade. This study also identifies that teenage self-concept has been constructed through various discourses, among other things good versus bad teenagers, role model seeking, and of teenage lifestyle.